2020
DOI: 10.30961/lr.2020.56.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Primary English Teachers’ AI Chatbots

Abstract: This study evaluates 17 AI English-language chatbots that were developed by nine groups of pre-service primary school teachers (N = 26). According to the achievement standards for the two grade bands in the curriculum (Grades 3-4 and 5-6: Ministry of Education, 2015), each group developed two chatbots, using Dialogflow API. The first and second chatbots were designed to talk the way a new friend would and in a specific situation, respectively. The chatbots have been found to provide opportunities for primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…M = 3.0 and Pol. M = 2.9) were more moderate concerning pre-service teachers' future intention to use chatbots, which may partly contradict some previous works [39,40]. Although the participants showed interest in learning more about chatbots, they seemed to prioritize human to human over human to chatbot communication, which is in line with Fryer et al [24].…”
Section: E-commercementioning
confidence: 44%
See 1 more Smart Citation
“…M = 3.0 and Pol. M = 2.9) were more moderate concerning pre-service teachers' future intention to use chatbots, which may partly contradict some previous works [39,40]. Although the participants showed interest in learning more about chatbots, they seemed to prioritize human to human over human to chatbot communication, which is in line with Fryer et al [24].…”
Section: E-commercementioning
confidence: 44%
“…However, research about pre-service teachers' perceptions concerning chatbot integration in language learning is scant. A notable exception is the study of Sung [39], who evaluated 17 AI English-language chatbots developed by nine groups of pre-service primary school teachers using the Dialogflow API. The results showed that pre-service teachers found chatbots useful to engage students in playful and interactive language practice.…”
Section: Chatbots In Language Learningmentioning
confidence: 99%
“…According to the findings of Pérez et al (2020), chatbots have the potential to facilitate learning in a manner comparable to that of a human teacher. In addition, Sung (2020) evaluates AI English-language chatbots and posits that they are anticipated to significantly contribute to achieving speaking and listening proficiency benchmarks.…”
Section: The Emergence Of Ai Technology In Educationmentioning
confidence: 99%
“…It will help the students to improve their speaking skills. Sung [36] has proposed a study to examine the performance of artificial intelligence-based English speaking chatbots.…”
Section: Computer-assisted Tutoring Systemsmentioning
confidence: 99%
“…Method Year [51] Online intelligent English teaching [52] An English network teaching [53] Perceptions on the impact of AI on English language learning [54] Chatbots in education [55] Network intelligent control and traffic optimization [4] Educational technology in English major college teaching [2] Acceptance determinants of 5G services [13] Chatbots applications in education [19] Task-oriented chatbot system [17] Chatbots in higher education [31] Human-computer interaction on IoT-based college physical education [43] College English teaching innovation under AI [33] Machine learning and neural network in English learning [39] Educational robot teaching resources using AI [40] College English teaching mode based on AI [47] Vocabulary intelligent tutoring system for second-grade latinx English learners [56] Understanding students' perceptions of AI teaching [57] AI-enabled routing in software-defined networking [1] Innovation in university education [5] Mobile-assisted language learning [7] Adult learners in distance education [12] Chatbots [20] Conversational agents for learning foreign languages [21] AI-based pronunciation checker [26] Prediction of learning styles in adaptive e-learning [30] Eco-environment construction of English teaching using AI [3] e strategy of college English mode based on 5G and AI [35] Chatbot using dialogflow [36] Preservice primary English teachers' AI chatbots [58] AI chatbot as a language learning medium [28] College English culture intelligence-aided teaching [49] AI in EFL context [50] AI in education [59] AI writing evaluation system in China CET…”
Section: Reference Nomentioning
confidence: 99%